APLIKASI PROGRAMMABLE LOGIC CONTROLLER SIMATIC SIEMENS PADA RUANGAN PEMBERSIH - Jusman Rahim (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2009)
Malang simulation tool is aimed to limit or eliminate the dust particles that may enter the room because of people entering into the selection. As has been regulated in terms of good drugs manufactttre (GMP, Good Practice manufactur) then the room cleaning is obligatory attached to reduce contamination of the product made, for our case is the pharmaceutical industry in order to give customer the good quality and safe products. After making the simulation tools and did some experiment, we can concluded that this simulation tool is working well and can be applied to real situations to make adjustments and course completion in order make more better results